The weakness and strength of existing takaful model in oil & gas sector - Puspa Liza, Ghazali; Zainudin, Awang; Shafieza, Sazali (2019)
This study is focusing on improvement a new Group Personal Accident (GPA) model by study the weakness and strength of existing model. Judging from the gap in the existing Group Personal Accident in mostly oil & gas Company, essentially this research was conducted with a focus scope on Oil and Gas Company in Malaysia for improvement Service Quality of Takaful Company and more beneficial on Safety at workplace to employee.